Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Terhadap Profesi Akuntan Pendidik - Jabbar, Malik Abdul; Cahyono, Dwi; Maharani, Astrid (Universitas Pendidikan Ganesha, 2020)
For the final semester students of the Faculty of Economics, Accounting study program who will approuch their graduation, they will have goals and plans that they will take after Sarjana Ekonomi (SE) degree. They will have several choices of their career interests according to the desires or underlying factors. As for several professions that can be chosen by accounting scholars, such as Akuntan Publik, Akuntan Pemerintah, Akuntan Intern, and Akuntan Pendidik. This study aims to analyze the factors that influence the interests of accounting students towards Akuntan Pendidik profession for undergraduate students in Jember Regency. The sample used was a number of fifth or seventh semester students in accounting students at Muhammadiyah University of Jember, University of Jember, and STIE Mandala Jember. The sample selection tested in this study uses SPPS software. The variables used in this study are Dependent Variable (Y) and Independent Variables (X). For independent variables in this study are Pengakuan Profesional, Lingkungan Kerja, and Gaji/Penghargaan Finansial. For the dependent variable, the interest of accounting students towards Akuntan Pendidik profession.